2003
DOI: 10.1518/hfes.45.2.218.27241
|View full text |Cite
|
Sign up to set email alerts
|

Speed-of-Processing and Driving Simulator Training Result in Improved Driving Performance

Abstract: Useful field of view, a measure of processing speed and spatial attention, can be improved with training. We evaluated the effects of this improvement on older adults' driving performance. Elderly adults participated in a speed-of-processing training program (N = 48), a traditional driver training program performed in a driving simulator (N = 22), or a low-risk reference group (N = 25). Before training, immediately after training or an equivalent time delay, and after an 18-month delay each participant was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
349
2
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(372 citation statements)
references
References 28 publications
16
349
2
5
Order By: Relevance
“…However, this significant interaction reflected a Bregression to the mean^and appeared to be due to a significant difference between the CT and CT + DS groups at baseline. Nevertheless, this result went against literature findings indicating gains in visual checking strategies, lane changing and indicator use after driving simulator training [40,42]. Contrary to our hypothesis, the driving simulator experience did not allow the transfer of training benefits to the road: participants who drove on the simulator did not perform better on the road than those who only completed the cognitive training program.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, this significant interaction reflected a Bregression to the mean^and appeared to be due to a significant difference between the CT and CT + DS groups at baseline. Nevertheless, this result went against literature findings indicating gains in visual checking strategies, lane changing and indicator use after driving simulator training [40,42]. Contrary to our hypothesis, the driving simulator experience did not allow the transfer of training benefits to the road: participants who drove on the simulator did not perform better on the road than those who only completed the cognitive training program.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the non-significant Group x Time interaction effect suggests that visual attention performances of the participants from both groups improved similarly with training. Hence, the driving simulator experience, as designed in this study, may not allow additional attentional benefits, as previously demonstrated by Roenker and colleagues [42]. Performances in the UFOV® test are associated with crash risk and also road (26) 60 (18) 48 (12) 58 (18) Sub-scores Visual attention 19 (4) 25 (5) 20 (4) 25 (6) Interaction with other road users 6 (4) 7 (4) 5 (3) 7 (4) Planning 13 (7) 14 (6) 11 (5) 11 ( CT cognitive training, CT + DS cognitive training + driving simulator experience.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…More important, in that study, Ball et al showed that UFOV is the strongest index to discriminate between crash-involved versus crash-free drivers: Older drivers (aged 55-90) with a significant reduction in the UFOV were six times more likely to be involved in one or more accident. It has been suggested to use UFOV as a predictor of driving performance (Vance, et al, 2006;Roenker et al 2003). These results provide a new approach for treating the reduced visual-attentional capability of certain young adults as well as older adults by means of training.…”
Section: Introductionmentioning
confidence: 99%